Caregiving burden and mental health problems among family caregivers of people with dementia in rural Uganda - Herbert E. Ainamani; Paul E. Alele; Godfrey Z. Rukundo; Samuel Maling; Edith K. Wakida; Celestino Obua; Alexander C. Tsai (Cambridge Prisms: Global Mental Health, 2020)
AbstractBackgroundAlzheimer's disease and related dementias are associated with increasing health burden in low- and middle-income countries. Less well-recognized is the potential health burden experienced by other affected individuals, such as family caregivers. In this study, we sought to profile the burden of care and its association with symptoms of depression and anxiety among informal caregivers of people living with dementia in rural southwestern Uganda.MethodWe conducted a cross-sectional study of 232 family caregivers of people with dementia. The key measured variables of interest were caregiving burden (Zarit Burden Index) and symptoms of depression and anxiety (Depression Anxiety Stress Scales). We fitted multivariable regression models specifying depression and anxiety symptoms as the primary outcomes of interest and caregiving burden as the primary explanatory variable of interest.ResultsFamily caregivers of people with dementia experience significant caregiving burden, with each item on the Zarit Burden Index endorsed by more than 70% of study participants. Nearly half [108 (47%)] of caregivers had Zarit Burden Interview scores >60, suggestive of severe caregiving burden. In multivariable regression models, we estimated a statistically significant positive association between caregiving burden and symptoms of both depression [b = 0.42; 95% confidence interval (CI) 0.34–0.49] and anxiety (b = 0.37; 95% CI 0.30–0.45).ConclusionFamily caregivers of people with dementia in rural Uganda experience a high caregiving burden, which is associated with symptoms of depression and anxiety. Interventions aimed at reducing caregiving burden may have important collateral mental health benefits.